The making of the American dream : an unconventional history of the United States from 1607 to 1900. - Kaplan, Lewis E. (Algora Pub., 2009)
Any history that touts itself as unconventional is bound to raise some hackles when it challenges traditional interpretations of our nation?s past. Yet history is continually under revision. This 2-volume work, covering America's first 300 years, differs from others in seeking to debunk numerous flattering and conventionally accepted myths. Reading between the lines of what we've all been taught as US history, the author probes a little deeper into what perhaps was never denied? but was never spelled out, either. Some inconvenient questions emerge. Was lust for land the driving force behind e.